Do Judicial Elections Impact the Perception of Impartiality? A Comparison of Bar Poll Ratings of Elected and Appointed Illinois Downstate and Collar County Trial Judges. (2nd April 2016) - McClure, Thomas E.
Abstract: This study compares the Illinois State Bar Association (ISBA) judicial poll impartiality scores of 256 elected and 381 appointed trial judges seated in 101 Illinois counties over an 18-year period at the conclusion of their first term of office. This article also analyzes the ISBA impartiality ratings of the subset of 126 elected judges and 100 appointed judges who were evaluated after serving 12 years in office. In both sets of circumstances, regression analyses revealed a significant negative relationship between elections and impartiality ratings given by the attorneys participating in the polls. Finally, this study compares the mean impartiality scores of the 49 individuals who served as both elected and appointed judges. This comparison reveals that these judges garnered lower impartiality ratings when they served as an elected judge compared to their ratings as an appointed judge.